Test of Chemical Compounds on Fruit Eggplant (Solanum Torvum) Room Temperature Storage LCMS and FTIR Methods - Helilusiatiningsih, Nunuk (Prosiding Seminar, 2021)
Eggplant Pokak (Solanum torvum), thrives in all parts of Indonesia, other names according to regional origin, namely eggplant sparrow, takokak, Popular Abroad under the name Turkey Berry.  Research on main eggplant explains that it functions to inhibit cancer cells, antimicrobial, anti-allergic, antioxidant, etc. The purpose of the experiment was to analyze the chemical components of eggplant pokak which were stored at room temperature for 3 days and fresh fruit. Experimental design used the LCMS method and functional groups the FTIR method. The results of the research on chemical compounds of eggplant pokak  contained 12 components of bioactive compounds (LCMS test)  were chlorogenic acid, 4-O-caffeoylquinic acid, 3-O-caffeoylquinic acid, 3-O-feruloylquinic acid, 5 -O-feruloyquinic acid, 3-O-feruloylquinic acid, 3,4,O-dicaffeoylquinic acid, 3,5-O-dicaffeoylquinic acid, 3-O-feruloylquinic acid, 5-O-feruloylquinic acid and putative dicaffeoylquinic acid and results FTIR test were  reinforced such as   OH,  CH, C=C,  C = C, NO2, CN, CO.